Analysis of the Determination of Hospital Tariff Rates for BPJS Patients Diagnosed with Typhoid Fever at Ananda Blitar General Hospital - Wisnu Winoto; Ratna Wardani; Agusta Dian Ellina (Ficco Public Health Journal, 2025)
Background: The determination of hospital tariffs is a crucial aspect in the sustainability of healthcare facility operations, especially within the payment system of the Social Security Agency for Health (BPJS Kesehatan) based on Indonesian Case-Based Groups (INA-CBGs). This study aims to analyze the influence of the type of medical services provided by doctors, length of stay (LOS), medication costs, and laboratory costs on hospital rates for BPJS patients diagnosed with typhoid fever at Ananda Blitar General Hospital. Methods: This study uses a quantitative method with a cross-sectional approach. The sample consisted of 291 patients selected through stratified random sampling based on the class of care. Secondary data were obtained from the BPJS e-Claim and the Hospital Management Information System (SIMRS) for the period from August 1, 2021, to July 31, 2024. The analysis was conducted using dummy linear regression to identify the influence of each variable on hospital rates. Results: The research results show that the type of medical services provided by doctors, LOS, medication costs, and laboratory costs have a significant impact on hospital rates with a significance value of 0.000 < (α=0.05). Conclusions: The results of the regression test show that the type of medical services provided by doctors has the greatest influence, followed by LOS, medication costs, and laboratory costs.